Cognitive Load Variability from Road Characteristics Should Influence a Safety Requirement for Vehicle Stopping Sight Distance. (November 2019) - Pennetti, Cody A.; Hollenback, Kelsey; Kim, Inki; Lambert, James H.
Current U.S. geometric road design standards are based on a prescribed value for a driver's perception-reaction time (a constant value of 2.5 seconds), which represents the time necessary for a driver to safely stop the vehicle to avoid a crash (referred to as a stopping sight distance); however, these standards fail to consider how road complexity, driver risk perception, and visual stimuli can influence perception-reaction time. With over a million vehicle fatalities a year (WHO, n.d.), it is necessary to investigate methods of improving driver safety. The influence of road characteristics is considered with some road design policies, but not currently applied to stopping sight distance. This paper introduces theoretical considerations for increasing perception-reaction time (and thereby adjusting speed limits or road geometry) based on roadway complexity (volume of vehicles, road geometry, pedestrian crossings, frequency of adverse weather conditions, or other conditions).